(untitled) (London Journal of Research In Management & Business, 2025)
This research, purely theoretical, highlights in a synthetic way the evolution of the most salient approaches of the concept of management from its genesis to its modern conception, through a numerous kind of schools, including the classical one centered on the administrative and scientific organization of work and the human relations one, whose ideology reacts against the excesses of the technical and scientific approach aiming to improve the work of employees and the satisfaction of their needs. Moreover, the comparison of the evolution of the management along with the leadership concept has revealed that the use and the perception of these two concepts have evolved according to the geo-economics and technological contexts that have marked the history of commercial and industrial relations, particularly within developed countries such as United States, Japan, France and UK. On one hand, some authors think that management and leadership are similar while others state that they are completely opposite on the other hand. Meanwhile, other writers argue that these notions are indeed two different courses of action, but complementary and cannot be isolated because of the dynamic aspect of todays organizations and their managerial implications.